PEMANFAATAN MICROSOFT WORD DALAM PEMBUATAN KARYA ILMIAH BAGI GURU DI MTS. AL-FURQON BANJARMASIN - Muthia Farida; Dian Agustini; Muhammad Rais Wathani (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
Improving the quality of teachers can be seen from the productivity of teachers inmaking scientific papers, either in the form of articles, books, learningmaterials, modules and so on. The lack of ability of teachers in the mastery of thesoftware that is devoted to the creation of the scientific works, making the trend ofteachers utilizing software already used, i.e. microsoft office especially is MicrosoftWord, but the use of this software is not yet utilizing features existing in it optimallyutilizes features, such as the creation of a table of contents automatically, automaticbibliography creation, creation of a list of table/list of pictures automatically automaticindex creation, Glosarry, Citation, and so on. Many teachers are still using manual wayto make it, but if the diitinjau usage of the time, of course this requires a lot more timeallocation primarily requires a very high precision.The teachers only know MS Word with basic features as thesoftware for typing, andmakes writing a simple, and yet know advanced features inMS Word that should beused to ease the writing of scientific papers as described earlier.